Competitive intensity in differently regulated men's football leagues: evidence from English premier league and German Bundesliga. Issue 5 (29th November 2022) - Wagner, Fabio; Schubert, Mathias; Preuss, Holger; Könecke, Thomas
Abstract : Purpose: The Premier League (PL) and the Bundesliga (BL) were chosen for this study due to their fundamentally different approaches to ownership regulation and the distribution of media revenues. Regulation in the PL is very liberal if compared to the BL's 50+1-rule. In the BL, the distribution of media revenues is mainly based on past performance, whereas equal distribution is dominant in the PL. The specific aim of this paper was a longitudinal analysis with a focus on the final outcome of the seasons. Design/methodology/approach: This study looks at competitive intensity (CI) in the men's BL and the English PL because it is a crucial indicator for the long-term success of a sports league and the participants. To calculate the CI of both leagues and of all relevant sub-competitions (championship, Champions League (CL), Europa League (EL), Conference League (CoL) and fight against relegation), a CI index (CII) model was generalised and applied for an examination period spanning from 1998/99 to 2020/21. Findings: Until 2008/09, seasonal CI in the BL was somewhat higher than in the PL. But afterwards, the BL's championship race's CI dropped considerably, while the PL's CI for qualification for the CL rose profoundly. Results also showed that the introduction of the CoL raised the leagues' CI indices. Originality/value: Besides a methodological contribution with the generalisation of the applied CI index model, the findings are discussed in the context of the above-mentioned regulatory and distribution mechanisms also taking into account the very current discussion regarding general regulatory changes within European football.